ETHICAL HERMENEUTICS AS A FRAMEWORK FOR RELIGIOUS MODERATION: A STUDY OF AL-IKLĪL FĪ MA’ĀNI AL-TANZĪL BY KH. MISBAH MUSTOFA - Achmad Azis Abidin; Rokhmah Ulfah; Eka Mulyo Yunus; Faza Nailil Muna Syahida (Universitas Nurul Jadid, 2025)
Religious extremism continues to pose a major challenge in contemporary Islamic societies, particularly in plural contexts where competing interpretations of the Qur’an often generate exclusivism and intolerance. While existing studies on religious moderation largely approach this issue from sociopolitical or policy-oriented perspectives, there remains a significant gap in understanding how moderation is constructed as an ethical-hermeneutical practice within local Qur’anic exegetical traditions. This study aims to analyze how KH. Misbah Mustofa formulates religious moderation (wasatiyyah) as an ethical hermeneutic in al-Iklīl fī Ma’āni al-Tanzīl, and to identify the moral principles and interpretive strategies underlying this framework. Employing a qualitative, library-based methodology, the research utilizes thematic content analysis of selected Qur’anic verses related to justice, balance, tolerance, and human responsibility as khalīfah fī al-ard. The findings reveal that KH. Misbah conceptualizes moderation not as a political compromise or ideological midpoint, but as a dynamic ethical process that integrates textual interpretation with moral reasoning and social accountability. Anchored in Qur’anic values such as ‘adālah (justice), ta’ādul (balance), and ta’āruf (mutual recognition), his tafsir presents moderation as a cultivated moral virtue capable of resisting both religious extremism and ethical relativism. This study contributes to contemporary Qur’anic studies by advancing ethical hermeneutics as a robust analytical framework for religious moderation, highlighting the intellectual significance of Indonesian pesantren-based tafsir in global discussions on Islamic ethics, pluralism, and social harmony.